(untitled) (SAARC Journal of Agriculture, 2014)
The present study was carried out to analyse the price spread and marketing efficiency of different milch cow marketing channels in the state level cattle fairs of Rajasthan. The study identified six milch cow marketing channels i.e., (1) Farmer Farmer, (2) Farmer Local Trader Farmer, (3) Farmer Local Trader, (4) Farmer Distant Trader Farmer, (5) Farmer Distant Trader and (6) Farmer Local Trader Distant Trader. Marketing efficiency and producer share in consumers rupee were the highest in channel 1 followed by channel 2 and channel 4 as price spread was the lowest in channel 1 followed by channel 2 and channel 4 across all three breed categories (non-descript, indigenous and cross-breed). Transportation cost was found to be the major cost component both for sellers and buyers in all the six milch cow marketing channels. Besides transportation, other major cost components were cost of feeding animals at fairs and miscellaneous expenses (including own expenditure). There were differences in the marketing costs across non-descript, indigenous and cross-breed both for sellers and buyers in all channels. The study suggested the need for government transportation facilities and adequate feeds and fodder availability at reasonable price during the cattle fairs. Above all, government should bring more number of local cattle fairs under the ambit of regulation to further improve the efficiency of livestock marketing system in the state. DOI: http://dx.doi.org/10.3329/sja.v12i1.21111 SAARC J. Agri., 12(1): 34-47 (2014)